Anti-Hyperglycemic and Hypoglycemic Activities of 80% Methanol Extract and Solvent Fractions of Ocimum lamiifolium Hochst Ex Benth. (Lamiaceae) Leaves in Mice - Tesfaye T; Teka F; Duga G; Obsa T; Dereje B; Makonnen E (Dove Medical Press, 2023)
Tilahun Tesfaye,1,2 Firehiwot Teka,3 Gudeta Duga,2 Temesgen Obsa,4 Beyene Dereje,5 Eyasu Makonnen1,6 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Science, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pharmacy, College of Medicine and Health Science, Ambo University, Ambo, Ethiopia; 3Department of Traditional and Modern Medicine Research Directorate, Ethiopian Public Health Institute, Addis Ababa, Ethiopia; 4Department of Pharmacology, School of Pharmacy, College of Medicine and Health Science, Jigjiga University, Jigjiga, Ethiopia; 5Department of Pharmacology, School of Medicine, College of Medicine and Health Science, Dire Dawa University, Dire Dawa, Ethiopia; 6Center for Innovative Drug Development and Therapeutic Trials for Africa (CDT-Africa), Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Tilahun Tesfaye, Email tilahuntesfaye21@gmail.comBackground: Globally, the prevalence of diabetes mellitus is rising. Due to the scarcity, high cost, and many adverse effects of modern treatments, traditional medicine is commonly used in rural areas to treat a variety of illnesses, including diabetes mellitus. The aim of this study was to assess the antihyperglycemic and hypoglycemic effects of Ocimum lamiifolium Hochst ex Benth leaves.Methods: A crude methanol 80% extract's and its solvent fractions' effects on healthy, oral glucose-given, and STZ-induced diabetic mice were examined. Swiss albino mice of either sex were assigned into sixteen groups, each containing six mice, for the OGTT and hypoglycemia tests. Male mice were used in the study, and they were divided into groups for the negative control (citrate buffer for diabetic mice), the normal control (Tween 2%), the test groups, and a positive control (glibenclamide) for the antihyperglycemic test in STZ (200 mg/kg body weight)-induced diabetic mice.Results: A crude 80% methanol extract of 200 mg/kg effectively lowered blood glucose levels (p < 0.05) and none of the fractions extracts caused hypoglycemia shock in norma mice. The aqueous residue at 100, 200, and 400 mg/kg, the n-butanol fraction at 100 and 200 mg/kg, and the chloroform fraction at 200 mg/kg demonstrated higher glucose tolerance in orally glucose-loaded mice (p < 0.05). The crude 400 mg/kg of an 80% methanol extract, 100 and 200 mg/kg of the n-butanol fraction, 200 and 400 mg/kg of the chloroform fraction, and 5 mg/kg of glibenclamide significantly reduced blood glucose levels in STZ-induced diabetic mice (p < 0.05).Conclusion: The current research demonstrates that a crude 80% methanol extract of Ocimum lamiifolium Hochst ex Benth leaves, as well as its solvent fractions, significantly reduce blood sugar levels in mice that are healthy, loaded with glucose, and streptozotocin induced diabetic mice.Keywords: blood glucose, diabetes mellitus, glibenclamide, hyperglycemia, Ocimum lamiifolium, oral glucose tolerance test, streptozotocin